2011
DOI: 10.4338/aci-2011-06-ra-0035
|View full text |Cite
|
Sign up to set email alerts
|

Sociotechnical Challenges of Developing an Interoperable Personal Health Record

Abstract: Objectives To analyze sociotechnical issues involved in the process of developing an interoperable commercial Personal Health Record (PHR) in a hospital setting, and to create guidelines for future PHR implementations. Methods This qualitative study utilized observational research and semi-structured interviews with 8 members of the hospital team, as gathered over a 28 week period of developing and adapting a vendor-based PHR at Lucile Packard Children’s Hospital at Stanford University. A grounded theory app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…Thus, it could be considered as a barrier that could slow the adoption of PHR. This finding is supported by other studies conducted in the United States [ 8 - 10 , 13 , 15 ]. Moreover, it was shown that integration at certain circumstances could present some challenges consistent with the literature [ 3 , 5 , 7 - 9 , 13 , 15 ] in terms of integrating PHR with multiple healthcare systems indicating interoperability as a critical challenge as well as healthcare providers' readiness to adopt the PHR [ 3 , 5 ] which was also a concern highlighted by the focus group participants.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, it could be considered as a barrier that could slow the adoption of PHR. This finding is supported by other studies conducted in the United States [ 8 - 10 , 13 , 15 ]. Moreover, it was shown that integration at certain circumstances could present some challenges consistent with the literature [ 3 , 5 , 7 - 9 , 13 , 15 ] in terms of integrating PHR with multiple healthcare systems indicating interoperability as a critical challenge as well as healthcare providers' readiness to adopt the PHR [ 3 , 5 ] which was also a concern highlighted by the focus group participants.…”
Section: Discussionsupporting
confidence: 89%
“…The Standalone PHR is through commercial online websites that allow patients to record their health behaviors. On the other hand, the Tethered PHR is usually linked to a specific organization through its Electronic Medical Record (EMR) to ensure patients' access (as read only) to their health information [ 2 - 6 , 10 - 12 ]. In theory, the PHR has the capabilities that allow patients to keep track of their health information, monitor and manage their illness especially in cases of chronic diseases, enhance efficiencies in appointment scheduling, medication refills, and improve the communication with healthcare providers for better quality of care [ 1 - 6 , 9 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Schnipper et al [ 92 ] included usability testing of both the clinician and patient interfaces. The remaining 14 studies assessed users’ subjective satisfaction and ease of use with questionnaires and/or interviews to evaluate overall adoption and utilization [ 11 , 38 , 45 , 47 , 48 , 64 , 65 , 73 , 82 , 88 , 89 , 91 , 97 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lucile Packard Children’s Hospital recently piloted development of a bidirectional link between a pediatric EMR and a commercially available, interoperable PHR. (29)(30)…”
Section: The Abundance Of Datamentioning
confidence: 99%